2014
DOI: 10.3109/10428194.2014.883073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinically important chromosomal aberrations in acute myeloid leukemia by array-based comparative genomic hybridization

Abstract: Array-based comparative genomic hybridization (aCGH) chromosomal analysis facilitates rapid detection of cytogenetic abnormalities previously undetectable by conventional cytogenetics. In this study, we analyze 48 uniformly treated acute myeloid leukemia (AML) patients by 44K aCGH and correlated the findings with clinical outcome. aCGH identified previously undetected aberrations, as small as 5 kb, of currently unknown significance. The 36.7 Mb minimally deleted region on chromosome 5 lies between 5q14.3 to 5q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…Our analysis also revealed high burden of CNVs in our cases, which contradict previous reports [35] [53]. However, these findings significantly support reports by Mehrotra et al and Jun et al whereby the studies observed more than two-fold of CNVs in their samples [48] [50]. Studies by Mehrotra et al and Jun et al, however, lacked systematic use of germline DNA and thus, there could be overestimation of somatic CNVs.…”
Section: Studies On Aml Using Array Cgh and Snp Arraysupporting
confidence: 68%
See 1 more Smart Citation
“…Our analysis also revealed high burden of CNVs in our cases, which contradict previous reports [35] [53]. However, these findings significantly support reports by Mehrotra et al and Jun et al whereby the studies observed more than two-fold of CNVs in their samples [48] [50]. Studies by Mehrotra et al and Jun et al, however, lacked systematic use of germline DNA and thus, there could be overestimation of somatic CNVs.…”
Section: Studies On Aml Using Array Cgh and Snp Arraysupporting
confidence: 68%
“…In another study by Mehrotra et al, 48 AML uniformly treated AML patients were tested with a custom-designed 4X44K, 60-mer oligonucleotide genomic array with genecentric whole genome coverage [50]. Mehrotra's research group detected a total of 170 CNVs and reported that frequencies of sub-microscopic aberrations were higher compared to whole chromosomal abnormalities.…”
Section: Studies On Aml Using Array Cgh and Snp Arraymentioning
confidence: 99%
“…Genomic DNA was extracted from bone marrow aspirate material using Gentra Puregene (Qiagen, Valencia, CA). The Cancer Cytogenomic Microarray Consortium (CCMC) 4x180K chip was used according to the manufacturer’s protocol (Agilent Technologies, Santa Clara, CA) as described previously [ 25 ]. The Agilent GeneChip microarray scanner was used for imaging and data analysis was performed using Cytogenomic workbench software.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, due to poor morphology and complexity of chromosomal abnormalities, such deletions may remain cryptic by karyotype analysis. In one study involving AML with a complex karyotype, CMA testing identified 17p deletions encompassing TP53 in 6% of additional cases in which they were not detected by conventional karyotype analysis [88].…”
Section: Accepted Manuscriptmentioning
confidence: 99%